Pembentukan Dan Pelatihan Kader Pos Kesehatan Pesantren Imam Adz-Dzahabi Kabupaten Kampar - Firdaus; Winarto, Winarto; Sukiandra, Riki; Sofian, Amru (LPPM UMRI, 2023)
Islamic Boarding School Health Post (POSKESTREN) is one form of community-based health efforts in the Islamic boarding school environment. The Imam Adz-Dzahabi Islamic Boarding School, which is located in Tambang District, Kampar Regency, Riau Province, already has a health post, but its management has not been implemented. The purpose of this service activity is to increase the knowledge of Poskestren managers and Santri Husada about the steps for establishing Poskestren, provide training in self-reflection surveys, and also provide training in the formulation of work programs. The socialization of Poskestren management and self-reflection survey training was well carried out in the presence of 33 participants, consisting of 3 Poskestren managers and 30 Santri Husada. There was an increase in participants' knowledge about the steps for establishing Poskestren. Participants can also practice self-reflection surveys and develop a program of Poskestren activities.